IDTI Dyes for Fluoride Anion Chemosensors - Yuan, Xinqiang; Shi, Xin; Wang, Cheng; Du, Yuqian; Jiang, Peng; Jiang, Xizhou; Sui, Yongqiang; Hao, Xiaoli; Li, Lin (Frontiers in Chemistry, 2020)
Fluoride anions play a key role in human health and chemical engineering, such as in organic synthesis and biological processes. The development of high-sensitivity naked-eye detection sensors for fluoride anions in organic solutions is crucial and challenging. In this study, IDTI was designed and used as a fluoride chemosensor for the first time. IDTI is a highly sensitive fluoride sensor with a detection limit of as low as 1×10⁻7 M. In addition, upon the reaction of IDTI with fluoride anions in a THF solution, color changes from red to yellow under ambient light and from purple to green under UV light were detectable by the naked eye. These studies indicate that IDTI is a promising fluoride chemosensor.